New Theatre for Old Homes (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
This paper approach the technical and aesthetic possibilities created by the online transmission platforms for the puppet theatre. In accord on a hypothesis launched by a theatrical director, the Covid-19 pandemic created a new manner of theatrical production and a “new art” too. If, on the one hand, we will verify that this “new art” reaffirms elements of traditional theatrical practice and aesthetics, on the other, we will note that it contains intriguing elements that referring, above all, to the use of theatre space. To develop this analysis, I will consider as a basis for discussion the show Crescer para Passarinho, produced by Coletivo Performers sem Fronteiras in 2020.
Keywords: shadow theater; online streaming theatre; theater space; creation process; pandemic